2018
DOI: 10.1029/2018gl078356
|View full text |Cite
|
Sign up to set email alerts
|

Greenland Ice Sheet: Higher Nonlinearity of Ice Flow Significantly Reduces Estimated Basal Motion

Abstract: In times of warming in polar regions, the prediction of ice sheet discharge is of utmost importance to society, because of its impact on sea level rise. In simulations the flow rate of ice is usually implemented as proportional to the differential stress to the power of the exponent n = 3. This exponent influences the softness of the modeled ice, as higher values would produce faster flow under equal stress. We show that the stress exponent, which best fits the observed state of the Greenland Ice Sheet, equals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
79
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(98 citation statements)
references
References 50 publications
19
79
0
Order By: Relevance
“…Ice rises archive their flow history in their characteristic internal stratigraphy (e.g. Conway et al, 1999;Nereson and Waddington, 2002;Drews et al, 2015), making them potentially suitable sites for ice-core drilling such as for the International Partnerships in Ice Core Sciences (IPICS) 2K and 40K Array (Brook et al, 2006). Due to very low deviatoric stresses near the bed of the divide region and the power law rheology of ice, the effective viscosity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Ice rises archive their flow history in their characteristic internal stratigraphy (e.g. Conway et al, 1999;Nereson and Waddington, 2002;Drews et al, 2015), making them potentially suitable sites for ice-core drilling such as for the International Partnerships in Ice Core Sciences (IPICS) 2K and 40K Array (Brook et al, 2006). Due to very low deviatoric stresses near the bed of the divide region and the power law rheology of ice, the effective viscosity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…concerning melting and basal conditions. In particular, Bons et al (2018) thorough analysis of observational data of the Greenland Ice Sheet supports a flow exponent of n = 4, not the standard value of n = 3. This is in line with recent experiments which allow for large ice deformations in the lab, a regime similar to ice flow in glaciers, which also finds n > 3 (Qi et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
“…Thorough analysis of the thickness, surface slope and velocities of the Greenland Ice Sheet, which are available through remote sensing, allow to relate the driving stress to the velocities and thus to infer the flow exponent n under realistic conditions. Bons et al (2018) find a flow exponent n = 4 in regions where sliding is negligible.…”
mentioning
confidence: 87%
“…CC BY 4.0 License. by many previous ice-rise divide studies, the commonly used exponent of the ice rheology law (n=3) is not able to reproduce the Raymond arch amplitudes from observations, but often a higher exponent (ni≈4.5) is chosen that better matches the arch amplitudes from observations (Martín et al, 2014;Drews et al, 2015;Bons et al, 2018). Moreover, Martín et al (2009a) showed that the commonly employed approximation of ice being an isotropic material in large-scale ice-sheet models is not valid at ice divides, where a preferential orientation of the ice crystals leads to enhanced ice deformation.…”
Section: Model Limitations 15mentioning
confidence: 99%
“…In this equation E is the enhancement factor, B is a viscosity parameter computed through an Arrhenius law, n is Glen's flow law parameter (n=3), and the effective strain rate is defined as˙ e 2 = tr(˙ 2 )/2. Although there is evidence that the Glen flow parameter is >3 (Bons et al, 2018), particularly near ice rises , we stick to the current modelling standard of n=3, because we focus on divide migration rather than Raymond arch amplitudes here. The same holds for the 20 enhancement factor, which is often used to account for anisotropic effects, but is set to 1 (isotropic conditions) in all simulations.…”
mentioning
confidence: 99%